Study on the Effects of Acupuncture in Alleviating Depression and Social Anxiety Induced by Chronic Pain in Patients - Li, Chenhao; Li, Yongfeng (Journal of Contemporary Medical Practice, 2025)
Objective: To investigate the efficacy of acupuncture in alleviating chronic pain, explore its relationship with depression and social anxiety in chronic pain patients, and clarify the therapeutic role of acupuncture. Methods: Between 2023 and July 2024, 126 patients were randomly selected from the acupuncture department of a traditional Chinese medicine hospital in Shaanxi Province. Questionnaires comprising the Numerical Rating Scale for Pain, Beck Depression Inventory (BDI), and Interpersonal Anxiety Scale (IAS) were administered. Results: Chronic pain severity positively correlated with depression (r = 0.218, P < 0.05), and depression positively correlated with social anxiety (r = 0.511, P < 0.05).The severity of chronic pain influenced an individual’s depression status (adjusted R²= 0.04, β = 1.039), while depression scores affected an individual’s social anxiety status (adjusted R²= 0.225, β = 0.404).Follow-up assessments indicated acupuncture’s impact on chronic pain, depression, and social anxiety, with the most pronounced effect on chronic pain and the least evident on social anxiety (chronic pain P=0.012, depression scores P=0.032, social anxiety P=0.046). Conclusion: Individuals with higher levels of chronic pain exhibited more severe depressive symptoms, and those with more severe depression also scored higher on social anxiety measures. Acupuncture treatment produced significant improvements in chronic pain, and as pain conditions improved during this process, patients’ depression and social anxiety also showed some degree of improvement.